Impact of stray-inductance imbalance on short-circuit capability of multi-chip SiC power modules. (November 2020) - Chou, K.; Isobe, T.; Mannen, T.
Abstract: This paper discusses whether short-circuit capability of multi-chip SiC-MOSFET power modules is affected by stray-inductance imbalance between the chips or not. Experimental power modules equipped with commercial 1.2-kV, 19-A SiC-MOSFET chips are designed and fabricated in three different internal layouts, and then short-circuit capability of the power modules is measured. The experimental results show that the significant effect of stray-inductance imbalance can be seen only for 20 ns after the short-circuit event start. As a result, this paper reveals that multi-chip power module design doesn't need to pay attention to imbalance of stray inductance from the perspective of the short-circuit robustness.